التحليل الجغرافي لمستويات الامن وعلاقتها بالامن بالأمن الصحي العراقي في ظل جائحة كورونا (Journal of the College of Basic Education, 2023)
Summary of the research:There is a relationship between health security and levels of security (national security, human security) in light of the Corona pandemic. Corona, as well as highlighting the comprehensive national security system and the impact of the pandemic on health security and Iraqi national security policies.Keywords: security, virus, corona, health security.